Moving sounds within the peripersonal space modulate the motor system. (April 2015) - Finisguerra, Alessandra; Canzoneri, Elisa; Serino, Andrea; Pozzo, Thierry; Bassolino, Michela
Abstract: Interactions between ourselves and the external world are mediated by a multisensory representation of the space surrounding the body, i.e. the peripersonal space (PPS). In particular, a special interplay is observed among tactile stimuli delivered on a body part, e.g. the hand, and visual or auditory external inputs presented close, but not far, from the same body part, e.g. within hand PPS. This coding of multisensory stimuli as a function of their distance from the hand has a role in upper limb actions. However, it remains unclear whether PPS representation affects the motor system only when stimuli occur specifically at the hand location or when they move within a continuous portion of space where the hand can potentially act. Here, in order to study these two alternatively hypotheses, we assessed the critical distance at which moving sounds have a direct effect on hand corticospinal excitability by using Transcranial Magnetic Stimulation (TMS). Specifically, TMS single pulses were delivered when a sound source was perceived at six different positions in space: from very close to subjects׳ hand (15 cm) to far away (90 cm). Moreover, sound direction was manipulated to test if stimuli approaching and receding from the hand might have the same relevance for the motor system. MEPs amplitude was enhanced when sounds were delivered within a limited distance from the hand (around 60 cm) as compared to when the sounds were beyond this space. This effect captures the spatial boundaries within which PPS representation modulates hand cortico-motor excitability. This spatially-dependent modulation of corticospinal activity was not further affected by the sound direction. Such findings support a strict link between the multisensory representation of the space around the body and the motor representation of potential approaching or defensive acts within that space. Highlights: We tested motor excitability when sounds approached or receded from the body. Excitability is higher when sounds are within ~60 cm from the hand. The effects are independent from the direction of the moving sound. Stimuli moving within peripersonal space are relevant for the hand motor system. Peripersonal space is not defined in metrical but in sensorimotor functional term.